2011
DOI: 10.1038/onc.2010.631
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-3 regulates MUC1 and EGFR cellular distribution and EGFR downstream pathways in pancreatic cancer cells

Abstract: MUC1 is a transmembrane glycoprotein which is typically expressed at the apical membrane of normal epithelial cells. In cancer cells, the over-expression of MUC1 and its aberrant localization around the cell membrane and in the cytoplasm favours its interaction with different protein partners such as epidermal growth factor receptor (EGFR) and can promote tumour proliferation through the activation of oncogenic signalling pathways. Our aims were to study the mechanisms inducing MUC1 cytoplasmic localization in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
79
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(89 citation statements)
references
References 54 publications
4
79
1
Order By: Relevance
“…Irrespective of other possible existing mechanisms, in the present study we have demonstrated -to the best of our knowledge, for the first time -that a decrease of galectin-3 plays a role in MUC1 up-regulation, in mammary cancer, suggestive of an indirect contribution to de-adhesion and in accordance to our in vivo observations. So far, the only existing study showing a role for galectin -3 in MUC1's regulation was that of Merlin et al,2011) in which galectin-3 knock-down, in a pancreatic cancer cell line, led to a decrease in MUC1 expression in accordance with their in vivo data from human pancreatic carcinoma where both galectin-3 and MUC1 are overexpressed in primary tumours. Furthermore, our data showing that MUC1 knock-down leads to decreased levels of galectin-3 imply that MUC-1 in turn is able to up-regulate galectin-3.…”
Section: B C D a B Asupporting
confidence: 52%
“…Irrespective of other possible existing mechanisms, in the present study we have demonstrated -to the best of our knowledge, for the first time -that a decrease of galectin-3 plays a role in MUC1 up-regulation, in mammary cancer, suggestive of an indirect contribution to de-adhesion and in accordance to our in vivo observations. So far, the only existing study showing a role for galectin -3 in MUC1's regulation was that of Merlin et al,2011) in which galectin-3 knock-down, in a pancreatic cancer cell line, led to a decrease in MUC1 expression in accordance with their in vivo data from human pancreatic carcinoma where both galectin-3 and MUC1 are overexpressed in primary tumours. Furthermore, our data showing that MUC1 knock-down leads to decreased levels of galectin-3 imply that MUC-1 in turn is able to up-regulate galectin-3.…”
Section: B C D a B Asupporting
confidence: 52%
“…For example, GM3, the ganglioside containing the sialyllactose epitope, has been reported to interact with EGFR and inhibit its kinase activity in a model supplemented with the GM3 glycolipid, and treatment with neuraminidase can rescue the autophosphorylation of EGFR (37). In addition, galectin-3 also can regulate the cellular trafficking and the level of surface EGFR through binding to the glycans on EGFR, and the binding can be blocked by sialylation on EGFR (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…The nuclear receptor is reported to interact with MUC1 and increase the level of chromatin-bound EGF receptor (Bitler et al 2010;Merlin et al 2011). MUC1 is a cell-surface protein that is known to interact with the receptor and promote receptor internalization.…”
Section: Erbb-1mentioning
confidence: 99%